HAK IJBAR DALAM HUKUM KELUARGA ISLAM - Nurhalisa; Basri, Rusdaya; Muchsin, Agus; Faiz, ABD Karim (Universitas Islam Negeri Alauddin Makassar, 2025)
Marriage in Islam, regulated by law and sharia principles, emphasizes the importance of the consent of the bride and groom. However, in Watang Pulu District, Sidenreng Rappang Regency, forced marriages, still occur as a result of the implementation of the right of ijbar. In the Shafi'i School, although the guardian has the right to marry his child, the marriage must be carried out based on consent, not coercion. This study uses a qualitative descriptive method to analyze the practice of forced marriage and its impact on children's mental and physical health. Observations and interviews reveal that forced marriages often end in divorce and unhappiness, ignore individual rights, and cause severe emotional distress to victims. This shows the need for law enforcement and a better understanding of rights in marriage to prevent this practice in society